THE REASONS OF THE MAIN CHARACTER IN USING SLANG WORDS IN DEADPOOL 2 MOVIE DIRECTED BY DAVID LEITCH - Maulani Pangestu (Wanastra: Jurnal Bahasa dan Sastra, 2019)
The objective of this study is to find out how many slang word found and reason the main character using slang word in Deadpool 2 movie directed by David Leitch. The analysis only focused on main character dialogues. The method used in this analysis is descriptive qualitative method with the library and internet research. The analysis comes with several processes. First, watched the movie several times to find out how many slang words used by main character. Second, take note of slang words found based on the theory of Coleman and then analyzing the reason main character using slang word based on the theory of Wijaya. The results of analysis found 66 data applied. The result of analysis also found how slang words can be used by main character to express his emotions.